A High-Resolution Digital Elevation Model in Combination With Water Table Depth and Continuous Soil Redox Potential Measurements Explain Soil Respiration and Soil Carbon Stocks at the ICOS Site Sorø - Callesen, Ingeborg; Brændholt, Andreas; Schrumpf, Marion; Vesterdal, Lars; Magnussen, Andreas; Vorenhout, Michel; Larsen, Klaus Steenberg (Frontiers in Forests and Global Change, 2021)
Quantification of activity data and emission factors for carbon (C) in inland wetland mineral soils (IWMS) lack suitable low cost indicators for key soil C processes in temperate forests. In a beech (Fagus sylvatica L.) forest near Sorø, Denmark, SOC stocks and the risk of losing pre-drainage legacy SOC were studied using a digital elevation model (0.4 m resolution), redox potential and soil respiration measurements. The results were compared with a digitized legacy soil map used in the national GHG reporting to UNFCCC. In upland, flat and sloping terrain, an aerobic soil environment (Eh > 400 mV) prevailed throughout most of the year, but in a peat-filled topographic depression (TD) anaerobic conditions (Eh < 400 mV) fully or sporadically occurred in the growing season, controlled by the ditching-affected water table. The relief included SOC rich TDs making up 18.9% of the area based on the ‘Filled sink’ algorithm (Saga GIS). In contrast, the peat cover on the legacy soil map was 8.2%. Furthermore, the mapped peat polygons were offset from the TDs defined by the DEM. The SOC stocks at 0 - 40 cm depth outside TDs (least squares mean 8.4 ± sem 0.3 kg C m-2) were significantly lower than within TDs (11.9 ± sem 0.5 kg C m-2). Average annual soil respiration increased linearly with the SOC stock by 0.06 kg C per kg SOC up to a SOC stock of 11 kg C m-2 to 20 cm depth, and a SOC loss of 0.23 ± se 0.10 kg C m-2 yr-1 was indicated inside the TD areas, close to the IPCC estimate of 0.26 kg C m-2 yr-1 for drained organic soils under forest. Our results show that continuous sensor-based monitoring of redox potential and shallow water tables linked with high-resolution DEMs offer the possibility to estimate the spatial extent of inland wetland mineral soils and their status as aerobic or anaerobic as indicated by iron rods with higher accuracy than previously. This underpins the potential use of such data for activity data mapping in Tier 3 greenhouse gas reporting.